PERKEMBANGAN PEMUKIMAN DI DAERAH INDRAMAYU - Saptono, Nanang (BRIN, 1995)
The beginning of the growth of the cities along the north coast of West Java was closely related to the fall of Malacca to the Portuguese in 1511. Since then, trade relations between the Portuguese and the Sundanese kingdom have intensified. This is because Sundanese provide a lot of commodity goods, especially pepper. In his description, Barros illustrates that the mountainous interior of Sunda is unlike the interior of Java. The main ports number six, namely Chiamo, Xaca-tra, or Caravam, Tangaram, Cheguide, Pondang, and Bantam.